PENGARUH KINERJA KEUANGAN TERHADAP MANAJEMEN LABA (Media Riset Akuntansi, 2022)
This study aims to examine the effect of dividend payments, profitability, and leverage on earnings management. The study population was LQ45 companies listed on the Indonesia Stock Exchange in 2016-2018, totaling 135 companies. The sampling technique uses purposive sampling method. Based on the sample size technique obtained 54. The method of data analysis uses multiple linear regression analysis with SPSS. The results show that dividend payments negatively affect earnings management; Leverage has a positive effect on earnings management, while profitability has no effect on earnings management